A Conceptual Framework Curriculum Evaluation Electrical Engineering Education - Nurulita Imansari; Eddy Sutadji (International Journal of Evaluation and Research in Education (IJERE), 2017)
This evaluation is a conceptual framework that has been analyzed in the hope that can help research related an evaluation of the curriculum. The Model of evaluation used was CIPPO model. CIPPO Model consists of context, input, process, product, and outcomes. On the dimension of the context includes the vision and mission of the study program, the purpose of the study program. On the input, dimension consists of learning achievements, curriculum structure, qualified lecturer, and course outline. On the dimensions of the process consists of academic activities, implementation of industry practice, PPL and KKN, facilities and infrastructure, learning strategies, resources and learning media and also learning evaluation. On the product, dimension consists of the value of the GPA and dimension outcomes consist of skills match the needs of the working world.